Improvement of Bearing Capacity of Shallow Foundation on Geotextile (Geosynthetics) Reinforced Soil - Hind Rafa; Enas Altalhe (AlQalam Journal of Medical and Applied Sciences, 2025)
An important first step in understanding the issue of structural settlement is the investigation of bearing capacity under footings subjected to static loads. The strength of the foundation soil is known to affect the bearing capacity of shallow foundations. When shallow foundations are erected upon weak soils, they face several issues. Therefore, Weak soils must be improved using soil improvement techniques, such as soil reinforcing systems, which improve the soil’s bearing capacity and decrease the settlement of structures. Many soil reinforcement methods have been developed. Some of the most commonly used techniques are: grouting, freezing, dewatering, compacting, soil mixing, geosynthetics, etc. Synthetic materials consisting of natural or polymeric materials are known as geosynthetics. such as geogrid, geotextile, geonet, and geocell are conventional reinforcement materials that can be used in three-dimensional structures, strips, or sheets in improved soil techniques. They may help with more environmentally friendly building projects and are simple to prepare and carry. The results of this review paper may be useful in knowing how to increase the bearing capacity of soil for shallow. The concept and principle of reinforcement of soil using foundations, and what are the ways to improve the ground with geosynthetics